Masalah Negara Vasal Majapahit - Machi Suhadi (Berkala Arkeologi, 1995)
Majapahit in the mid-14th century AD controlled the entire archipelago and several countries in Southeast Asia, including Siam, Campa, Cambodia, and Singhanagari. Prapanca, as the compiler of the Nagarakertagama manuscript, explained the existence of these vassal countries in the 13th to 15th stanzas. Prapanca also explained how to manage the relationship between Majapahit and its vassal countries and how to collect tribute from the vassal state. This narrative shows that Majapahit binds relations with vassal states in a unique way. This method was not carried out by colonialism but by establishing partnerships that were equal or equal (term: mitreka satata). In such an alliance, allegiance to the semitrail is required. Loyal partners will remain protected while treasonous partners will be oppressed by Majapahit.